Third Order Nonlinear Optical Properties of Urea Salicylic Acid for Phot Ionic Applications - Andal , C.; Murugakoothan, P. (Challenges and Advances in Chemical Science Vol. 9, 2022)
In the present work, the single crystal of urea salicylic acid was grown by slow evaporation method using the mixed solvent of water and ethanol. Slow evaporation was used to create an organic non-linear optical crystal of urea salicylic acid using a mixed solvent of ethanol and water in an equal ratio. The lattice parameters of urea salicylic acid crystal were obtained by single X-ray diffraction study. The optical transmittance study revealed the good transmission window of the urea-salicylic acid and its suitability for optical applications. The nonI linear refractive index, , absorption coefficient, and third order susceptibility, have been measured through the Z-scan technique with He-Ne laser at . The grown urea salicylic acid crystal exhibits two photon absorption and self-defocussing performance. The Z-scan approach validated the self-defocusing nature and two photon absorption process of the produced urea salicylic acid crystal. As a result, the crystal of urea salicylic acid is a good option for optoelectronic applications.